Continuous Wear of Night and Day Orthosis Is a Key Factor for Improvement of Fixed Equinus Deformity after the Transverse Vulpius Procedure - Mathis Wegner; Katharina I. Koyro; Louisa Kosegarten; Anna Kathrin Hell; Heiko M. Lorenz; Volker Diedrichs; Sebastian Lippross (MDPI AG, 2022)
Background: Equinus foot deformity is secondary to either spasticity or contracture of the gastrocnemius-soleus complex. The plantar flexion is basically treated conservatively; several different surgical methods have been discussed. This paper focuses on the improvement of passive ankle dorsiflexion after a transverse Vulpius procedure in equinus foot deformity. Additionally, the influence of consequent postoperative wear of orthosis on the improvement of ankle range of motion was investigated. Methods: In total, 41 patients with neuromuscular impairment and 59 equinus feet deformities were surgically treated by using a transverse Vulpius procedure. A total of 19 female patients and 22 male patients with a mean age at surgery of 10.18 years (2 to 31) were included. Mean follow-up took place 12.26 ± 7.95 months after surgery. Passive ankle dorsiflexion was measured and subjective patients' satisfaction was assessed. Results: Range of motion, measured as the maximum of passive ankle joint dorsiflexion, improved significantly from −8° ± 5.9° to 11.1° ± 6.7° directly after surgery to 16.2° ± 10.7° at follow-up. The improvement of passive ankle dorsiflexion was significantly associated with the continuous wearing of night and day orthosis (p = 0.0045). Patient subjective satisfaction was very high. Conclusion: A transverse Vulpius procedure for aponeurotic gastrocnemius and soleus muscle lengthening of equinus foot deformity resulted in a significant improvement of passive ankle dorsiflexion. Positive surgical results correlated to a continuous use of orthotic devices.